The Effect of Workforce Diversity on Employee Performance: Conceptual Framework - Al-Ahmad, Rafa Sufian; Alkhawlani, Dr. Mohammed Abdullah Ali (IJRDO - Journal of Business Management, 2017)
The subject matter of this paper is workforce diversity. Diversity in the workplace may result in deficient communication and conflict if employers fail to manage it. Many organizations observe gender, ethnicity, and education background as the most commonly diversified demographic variables among its workforce. Accordingly, this paper identifies the conceptual framework adapted to investigate the effect of workforce diversity on employee performance in Al-Madinah International University (MEDIU) in Malaysia. Hypotheses and conceptual structure have been built depending on the empirical studies and the results show a statistically significant effect of the three variables toward employee performance.